Designing a GaN-Based 1x2 Optical Power Splitter Using Rectangular Waveguide Coupling - Franata, Nauval; Ali Setyo Yudono, Muchtar; Ramadhani, Ahmad; Verlaili Erlindriyani, Ratu (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
The need for compact and efficient optical power splitters is becoming increasingly urgent due to the growing demand for integrated photonic devices, which are essential in fields like optical interconnects and sensing. This study addresses the issue by focusing on the design and analysis of a GaN based 1x2 optical power splitter that employs rectangular waveguide coupling. The primary aim of the research is to evaluate how the number of rectangular waveguide couplings affects the performance of the power splitter, particularly in terms of splitting angle and excess loss. To achieve this, simulations were conducted using the finite-difference time-domain (FDTD) method. The design was tested with three configurations: three, five, and seven rectangular waveguides. The research design follows a structured simulation approach, where the FDTD method was employed to explore the impact of varying the number of rectangular waveguides. The process involves systematically altering the number of coupling sections and analyzing the resulting output. The 3D optical power distribution and the optical field intensity at the splitter output for each design were examined. Additionally, the excess loss distribution over the wavelength range of 1500 nm to 1600 nm was determined, demonstrating the potential of the proposed designs for optical communication applications. This data analysis enabled the researchers to evaluate the performance of each configuration. Notably, as the number of waveguides increased, the splitting angle became wider, but this was accompanied by a rise in excess loss. These findings demonstrate the potential of the proposed design for practical applications. Future studies could explore further optimization and real-world implementation.